2020
DOI: 10.21203/rs.2.21181/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating Neutrophil-to-Lymphocyte Ratio at Admission Predicts the Long-Term Outcome in Acute Traumatic Cervical Spinal Cord Injury Patients

Abstract: Background: The prognostic value of Neutrophil-to-Lymphocyte Ratio (NLR) for the outcome of acute cervical traumatic spinal cord injury (tSCI) patients has rarely been studied by now throughout the world. Methods: We performed a single-center retrospective cohort study to evaluate the prognostic value of NLR from peripheral whole blood count in patients with acute cervical tSCI. Patients within 6 hours of acute cervical tSCI treated between Dec 2008 and May 2018 in Huashan Hospital of Fudan University were enr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Few articles have conducted detailed studies on such patients. Several recent clinical studies have shown that inflammatory indicators after TBI, such as NLR and PLR, play important roles in predicting the clinical outcomes of neurotraumatic diseases (37)(38)(39)(40)(41). For example, a study by Chen et al based on 688 cases of severe head trauma showed that 508 cases (73.8%) of patients with poor prognosis 1 year after head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Few articles have conducted detailed studies on such patients. Several recent clinical studies have shown that inflammatory indicators after TBI, such as NLR and PLR, play important roles in predicting the clinical outcomes of neurotraumatic diseases (37)(38)(39)(40)(41). For example, a study by Chen et al based on 688 cases of severe head trauma showed that 508 cases (73.8%) of patients with poor prognosis 1 year after head trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the breakdown of the blood-brain barrier after human SCI, the peripheral circulation communicates with the SCI area. When immune cells in the blood infiltrate the SCI area, the immune status in the circulating blood also changes [25,26]. The blood-brain barrier is also destroyed after SCI in mice [27,28].…”
Section: Discussionmentioning
confidence: 99%